THE ARTISTIC INTERPRETATION OF FEMALE IMAGES IN THE WORKS OF KATHERINE MANSFIELD - Ismatillaeva Mokhinur Sayfiddin kizi (Journal of Applied Science and Social Science, 2026)
This article examines the representation of female characters in the short stories of Katherine Mansfield from a modernist and psychological perspective. It highlights how Mansfield departs from traditional depictions of women by presenting them as complex psychological entities rather than merely social roles. The study focuses on themes such as inner conflict, loneliness, social pressure, and implicit resistance, as well as key poetic devices including symbolism, stream of consciousness, and open endings.